Structure of piatã palisadegrass deferred for two periods and fertilised with nitrogen - Rocha, Gabriel de Oliveira; Santos, Manoel Eduardo Rozalino; Vilela, Hélio Henrique; Carvalho, Bruno Humberto Rezende; Sousa, Braulio Maia de Lana; Fagundes, Jailson Lara; Backes, Alfredo Acosta; Fontes, Pryanka Thuyra Nascimento (Semina: Ciências Agrárias, 2020)
The deferred pasture structure determines the consumption and performance of grazing animals and, in addition, can be influenced by the duration of the deferment period and nitrogen (N) fertilisation. The objective of this work was to evaluate the structural characteristics of Brachiaria brizantha syn. Urochloa brizantha cv. Piatã (piatã palisadegrass) deferred for two periods (79 and 127 days) and with four N doses (0, 40, 80 and 120 kg ha-1) in the Zona da Mata of Minas Gerais, Brazil. The experimental design involved complete randomised blocks and a subdivided plot scheme, with three replications. The 127-day period of deferment resulted in a higher forage mass, falling index, stem percentage and density, but a lower number of tillers, percentage and volumetric density of live leaf blade. The N dose increment, in general, worsened the structural characteristics of the piatã palisadegrass deferred for 127 days. However, with the 79-day period, the N fertilisation increased the volumetric density of live leaf blades and reduced the stem percentage in the forage mass. As a preliminary recommendation, piatã palisadegrass can be deferred for 79 days and fertilised with up to 90 kg ha-1 of N in the region of Zona da Mata de Minas Gerais, Brazil.